An experimental investigation design of a bidirectional DC-DC buck-boost converter for PV battery charger system - Benlahbib, Boualam; Dahbi, Abedeljalil; Fares, Bennaceur; Lakhdari, Abelkader; Bouarroudj, Noureddine; Mekhilef, Saad; Abdelkrim, Thameur (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The aim of this paper is to present a bidirectional DC-DC buck-boost converter design that is specifically intended for use with storage batteries in a PV system. The primary purpose of the batteries is to mitigate the unpredictable and intermittent nature of renewable energy sources. To achieve this, a DC-DC converter is used in buck mode during daylight hours to charge the batteries with power derived from the PV system. If the photovoltaic energy source is unavailable, the batteries can discharge to power the DC load through the converter in boost mode. Therefore, the bi-directional DC/DC converter, which has a high-power capacity, manages the power storage system. To this end, the paper describes the design and implementation of both the power circuit board and drive circuit board of the buck-boost converter, taking into account the rated current, voltage, and power. Finally, the effectiveness and efficiency of the designed converter are verified through experimental tests carried out in both charge and discharge modes, with results demonstrating the validity and efficiency of the converter.